2020
DOI: 10.1111/poms.13116
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Value in Vertically Integrated Power‐to‐Gas Energy Systems

Abstract: In vertically integrated energy systems, integration frequently entails operational gains that must be traded off against the requisite cost of capacity investments. In the context of the model analyzed in this study, the operational gains are subject to inherent volatility in both the price and the output of the intermediate product transferred within the vertically integrated structure. Our model framework provides necessary and sufficient conditions for the value (NPV) of an integrated system to exceed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…Several promising avenues for future research emerge from our analysis. Earlier work has shown that the economics of electrolyzers can be improved by vertically integrating them with upstream renewable energy sources in order to achieve operational synergies 44 . It remains to be seen to what extent the addition of a renewable power source, beyond purchases from the grid, would improve the capacity utilization of a reversible PtG system and, therefore, lower the corresponding break-even values.…”
Section: Discussionmentioning
confidence: 99%
“…Several promising avenues for future research emerge from our analysis. Earlier work has shown that the economics of electrolyzers can be improved by vertically integrating them with upstream renewable energy sources in order to achieve operational synergies 44 . It remains to be seen to what extent the addition of a renewable power source, beyond purchases from the grid, would improve the capacity utilization of a reversible PtG system and, therefore, lower the corresponding break-even values.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, regulators could revisit markups on wholesale electricity prices, such as taxes and fees, that may impede storage investments through the curtailment of available revenue streams in a jurisdiction. For instance, before the modification of the Renewable Energy Act in 2017, storage facilities in Germany were considered as final consumers and, consequently, paid all regulatory price markups for the electricity used for charging ( EEG, 2017 ; Glenk and Reichelstein, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In estimating the learning curve for PEM electrolyzers, we rely on global average system prices that were hand-collected from journal articles, technical reports, and interviews with manufacturers (Glenk and Reichelstein 2020 ). Detailed information regarding the underlying manufacturing costs has remained scarce.…”
Section: Dynamics Of System Pricesmentioning
confidence: 99%
“…For the electrolyzer to operate efficiently, the conversion value of hydrogen, defined as the amount of hydrogen obtained per kWh less any ancillary expenses for iodized water, must at any given hour exceed the price of electricity at that time. The contribution margin of hydrogen thus varies over time and hinges on the price of electricity as well as the time-invariant conversion rate that determines the number of kilograms of hydrogen obtained from one kWh of electricity (Glenk and Reichelstein 2020 ).…”
Section: Dynamics Of the Levelized Cost Of Energymentioning
confidence: 99%